PEMIKIRAN EKONOMI M. UMER CHAPRA - Anindya Aryu Inayati (University of Darussalam Gontor, 2013)
M. Umer Chapra’s Thought in economics is a blend of traditional sciences, theology and modern economics sciences. His thinking is dominated by macro economic sector because he was widely occupied in the world economy. His thinking are including the concept of falah , hayyahtayyibah and Muslims economic challenges, monetary policy, the Islamic financial institutions which is concerned to the central bank and its policies, and the concept of welfare states according to Islam. Like the other Muslim economists, Chapra hammered at moral as the way of reaching fair and healthy economy. The privileged of M. Umer Chapra thought is the ability to mix and match between the Western economic concepts with Islamic values. He was awarded as the ‘ success Islamic scholar ‘. While his slight shortage is in the attitude of tolerance towards Western financial instruments. This attitude is the impact of his understanding of the world economy, that may not be erased from these instruments except gradually and slowly. Although Chapra realizes that the Islamic economic system can deliver socio - economic justice to the world and become a solution for the failure of the capitalist and socialist economic systems.